Treatments for kinesiophobia in people with chronic pain: A scoping review - Bordeleau, Martine; Vincenot, Matthieu; Lefevre, Salomé; Duport, Arnaud; Seggio, Lucas; Breton, Tomy; Lelard, Thierry; Serra, Eric; Roussel, Nathalie; Neves, Jeremy Fonseca Das; Léonard, Guillaume (Frontiers in Behavioral Neuroscience, 2022)
Kinesiophobia is associated with pain intensity in people suffering from chronic pain. The number of publications highlighting this relationship has increased significantly in recent years, emphasizing the importance of investigating and synthesizing research evidence on this topic. The purpose of this scoping review was to answer the following questions: 1) What types of interventions have been or are currently being studied in randomized controlled trials for the management of kinesiophobia in patients with chronic pain? 2) What chronic pain conditions are targeted by these interventions? 3) What assessment tools for kinesiophobia are used in these interventions? According to the studies reviewed, 1) physical exercise is the most commonly used approach for managing irrational fear of movement, 2) interventions for kinesiophobia have primarily focused on musculoskeletal pain conditions, particularly low back pain and neck pain, and 3) the Tampa Scale of Kinesiophobia is the most commonly used tool for measuring kinesiophobia. Future randomized controlled trials should consider multidisciplinary interventions that can help patients confront their irrational fear of movement while taking into account the patient's personal biological, psychological, and social experiences with pain and kinesiophobia.